Analisis Penggunaan Alokasi Dana Kampung dalam Pembangunan Kampung Pesayan Kecamatan Sambaliung Kabupaten Berau - Muhammad Fathrisal Hasbullah; Anwar Alaydrus; Melati Dama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This research was conducted in Berau District, located in Pesayan Village, Sambaliung District. This type of research is descriptive qualitative. The research was carried out in several stages, namely field research using observation, interview and documentation methods as well as library research. Furthermore, the data obtained will be analyzed descriptively qualitatively. This research is to find out the use of Village Fund Allocations carried out by the Village Government in the Development of Pesayan Village. The development of Pesayan Village includes several stages, namely deliberations to take ideas that are carried out by the local RT, then year-end deliberations on the Government Work Plan (RKP) and the results of the proposals will be included in the Village Expenditure Budget (APBK). The results of research conducted in Pesayan Village that Village Fund Allocations for physical development have only been realized for the construction of village halls and pipelines; the remaining Village Fund Allocations are focused on village government administration. Meanwhile, for non-physical development, it is realized using Village Allocation Funds but instead using Village Funds due to instructions from the District itself but still based on regulations. For the supporting factors in carrying out the development of Pesayan Village, namely the presence of Natural Resources and also Human Resources, and for the inhibiting factors the geographical conditions of Pesayan Village are widespread.